ALIRAN JABARIYAH DAN IMPLIKASINYA DALAM PEMBANGUNAN KARAKTER SOSIAL - Arifan Ananda; Nunu Burhanuddin (CV. Adiba Aisha Amira, 2023)
This article delves into the realm of Islamic thought, specifically exploring the domain of Kalam, often referred to as the science of theological discourse. Kalam, literally meaning